Nudging Altruism by Color: Blue or Red? - Nie, Xinyu; Lin, Han; Tu, Juan; Fan, Jiahe; Wu, Pingping (Frontiers in Psychology, 2020)
Altruism can be spontaneously aroused by environmental factors. However, the mechanism behind these factors is subject to debate. We carried out a study of laboratory experiment using computer-based Mouselab method to determine the mechanism. We found that different colors altered the altruistic behaviors of people. Specifically, blue enhanced altruism, whereas red discouraged altruism. We used a process-tracing technique to monitor the selection of an adaptive strategy and demonstrate that different colors can simulate changes in information acquisition and then lead to the corresponding behaviors. The results suggested that the decision heuristic plays a mediating role in the link between colors and individual altruistic behaviors.